Cyclooxygenase production of PGE2 promotes phagocyte control of A. fumigatus hyphal growth in larval zebrafish. - Savini Thrikawala (PLoS Pathogens, 2022)
Invasive aspergillosis is a common opportunistic infection, causing >50% mortality in infected immunocompromised patients. The specific molecular mechanisms of the innate immune system that prevent pathogenesis of invasive aspergillosis in immunocompetent individuals are not fully understood. Here, we used a zebrafish larva-Aspergillus infection model to identify cyclooxygenase (COX) enzyme signaling as one mechanism that promotes host survival. Larvae exposed to the pan-COX inhibitor indomethacin succumb to infection at a significantly higher rate than control larvae. COX signaling is both macrophage- and neutrophil-mediated. However, indomethacin treatment has no effect on phagocyte recruitment. Instead, COX signaling promotes phagocyte-mediated inhibition of germination and invasive hyphal growth. Increased germination and invasive hyphal growth is also observed in infected F0 crispant larvae with mutations in genes encoding for COX enzymes (ptgs2a/b). Protective COX-mediated signaling requires the receptor EP2 and exogenous prostaglandin E2 (PGE2) rescues indomethacin-induced decreased immune control of fungal growth. Collectively, we find that COX signaling activates the PGE2-EP2 pathway to increase control A. fumigatus hyphal growth by phagocytes in zebrafish larvae.